ESTUDOS DE TAXONOMIA INTEGRATIVA DO COMPLEXO Hoplias malabaricus (Bloch, 1794) NA BACIA AMAZÔNICA E DRENAGENS ADJACENTES - (:unkn) unknown (UNIVERSIDADE FEDERAL DO OESTE DO PARÁ, 2020)
Hoplias malabaricus is a species complex widespread from Northern to Southern South America continent. This group might constitute a good model for investigations of historical biogeographic events and the actual patterns of genetic structuring driving the ichthyofauna in the Neotropical freshwater systems. However, it is limited because of the confused taxonomy and the several cryptic species hidden in the complex. In this work, based on morphological and molecular evidence, we extend the distribution of H. misionera, which was only known from Uruguay, Paraná and Paraguay River basins. We also recognized the true H. malabaricus species and performed a population genetics analysis in this lineage. DNA barcoding revealed three to eight candidate species from the H. malabaricus complex inhabiting the study area. The largest clade recovered (BIN ABZ3047) was assumed as the true H. malabaricus sensu stricto. This species is structured in six population units: 1) Madeira River Basin (MRB), 2) Guiana Shields drainages (GSD), 3) Western Northeast Atlantic Basin (WNAB), 4) Tapajós River Basin (TRB), 5) Lower Amazonas River confluences (LARC) and 6) São Francisco River Basin (SFRB). The populations TBR and SFRB were most differentiated and showed demographic fluctuations, where the later showed evidence of declining.
Keywords: América do Sul; Biogeografia; Diversificação; Hoplias; Rio Amazonas; GENÉTICA E CONSERVAÇÃO DA BIODIVERSIDADE; ESTUDOS E MANEJOS DOS ECOSSISTEMAS AMAZÔNICOS